Overexpression of ZEB2‐AS1 promotes epithelial‐to‐mesenchymal transition and metastasis by stabilizing ZEB2 mRNA in head neck squamous cell carcinoma. Issue 6 (4th April 2019) - Diao, Pengfei; Ge, Han; Song, Yue; Wu, Yaping; Li, Jin; Li, Zhongwu; Yang, Jianrong; Wang, Yanling; Cheng, Jie
Abstract: The long noncoding RNAs (lncRNAs) have been increasingly appreciated as key players underlying tumourigenesis and hold great potentials as prognostic biomarkers and therapeutic targets. However, their roles in head neck squamous cell carcinoma (HNSCC) have remained incompletely known. Here, we sought to reveal the oncogenic roles and clinical significance of a tumour‐associated lncRNA, zinc finger E‐box binding homeobox 2 antisense RNA 1 (ZEB2‐AS1), in HNSCC. ZEB2‐AS1 was aberrantly overexpressed in a fraction of HNSCC samples. Its overexpression significantly associated with large tumour size, cervical node metastasis and reduced overall and disease‐free survival. Antisense oligonucleotides (ASO)‐mediated ZEB2‐AS1 depletion markedly inhibited cell proliferation, migration and invasion while triggered apoptosis in HNSCC cells in part via modulating ZEB2 mRNA stability. Enforced overexpression of ZEB2 largely attenuated the phenotypic changes resulted from ZEB2‐AS1 inhibition except the impaired cell proliferation. In addition, ZEB2‐AS1 was required for TGF‐β1‐induced epithelial‐mesenchymal transition (EMT) in vitro. Significantly reduced tumour growth and lung metastasis were observed in ZEB2‐AS1‐depleted cells in HNSCC xenograft animal models. Taken together, our findings reveal that overexpression of ZEB2‐AS1 associates with tumour aggressiveness and unfavourable prognosis by serving as a putative oncogenic lncRNA and a novel prognostic biomarker in HNSCC.